2009
DOI: 10.1103/physreve.80.011601
|View full text |Cite
|
Sign up to set email alerts
|

Chiral segregation in three microscopic statistical-mechanical models

Abstract: We consider three microscopic model molecular systems, each containing an equimolar mixture of a chiral molecule and its nonsuperimposable mirror image. The molecules in each model are assumed to lie on a thin film in such a way that they occupy the sites of a honeycomb lattice. Although neither enantiomorph is externally favored at low temperatures, we prove that for one range of interactions, chiral segregation into ordered phases containing a single enantiomorph occurs for two of the models and, in a second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…To explore chiral ordering in adsorbed phases different theoretical methods have been used including Monte Carlo (MC) (Popa and Paci 2013;Perusquía et al 2005;Martí-nez-González et al 2014;Paci et al 2007) simulations and statistical-mechanical calculations (Medved' et al 2009(Medved' et al , 2010(Medved' et al , 2015. In this work we rely on the first method and build a MC model of the surface-confined self-assembly of simple five-membered prochiral molecules.…”
Section: Simulationsmentioning
confidence: 99%
“…To explore chiral ordering in adsorbed phases different theoretical methods have been used including Monte Carlo (MC) (Popa and Paci 2013;Perusquía et al 2005;Martí-nez-González et al 2014;Paci et al 2007) simulations and statistical-mechanical calculations (Medved' et al 2009(Medved' et al , 2010(Medved' et al , 2015. In this work we rely on the first method and build a MC model of the surface-confined self-assembly of simple five-membered prochiral molecules.…”
Section: Simulationsmentioning
confidence: 99%
“…In order to understand and predict the chiral separation in adsorbed overlayers, one can use theoretical methods such as the Monte Carlo (MC) simulation method. MC simulations have been performed for a variety of simplified molecular chiral structures adsorbed on energetically homogeneous surfaces, including bent needles [5], tripods [6] and other polyatomic molecules [7,8]. These studies have demonstrated that the main effect on the chiral separation exert: density of the adsorbate [9], geometry of the molecules and intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, they studied the chiral separation of the Andelman de Gennes 7 model adsorbed to a lattice using different kinds of interactions, including van der Waals and electrostatics, 12 and different ranges of interactions. 13 In both cases, they obtained chiral separation under specific conditions.…”
Section: Introductionmentioning
confidence: 99%